A repeated principal-agent model with on-the-job search - Daniel Herbold (Goethe University Frankfurt, SAFE - Sustainable Architecture for Finance in Europe, 2014)
This paper analyzes how on-the-job search (OJS) by an agent impacts the moral hazard problem in a repeated principal-agent relationship. OJS is found to constitute a source of agency costs because efficient search incentives require that the agent receives all gains from trade. Further, the optimal incentive contract with OJS matches the design of empirically observed compensation contracts more accurately than models that ignore OJS. In particular, the optimal contract entails excessive performance pay plus efficiency wages. Efficiency wages reduce the opportunity costs of work effort and hence serve as a complement to bonuses. Thus, the model offers a novel explanation for the use of efficiency wages. When allowing for renegotiation, the model generates wage and turnover dynamics that are consistent with empirical evidence. I argue that the model contributes to explaining the concomitant rise in the use of performance pay and in competition for high-skill workers during the last three decades.
Keywords: C73; D82; D86; J33; L14; 330; Repeated Principal-Agent Model; On-the-Job Search; Moral Hazard; Multitasking; Efficiency Wages